Chemically Defined Medium for the Growth of Clostridium perfringens - Riha, William E. (1971)
A defined medium which supports growth of Clostridium perfringens at low inoculum levels was developed. Generation time for strain 8797 was 1.5 times greater than previously reported for growth in purged fluid thioglycolate medium.